1995
DOI: 10.1002/art.1790080417
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal conditions and employment

Abstract: Objective. To describe the prevalence, incidence, and correlates of work disability among persons with musculoskeletal conditions.Methods. Literature review and analysis of the Health and Retirement Survey, a national, probability sample of community-based adults ages 51-62.Results. Clinical samples of persons with RA report work disability rates of 52 % to 60%. Communitybased studies of persons with a broad range of musculoskeletal conditions find work disability rates of 38% to 7.270, depending on the mix of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 14 publications
(17 reference statements)
3
30
1
3
Order By: Relevance
“…Table 6 presents findings from national samples of older adults living in the community on disability measures in the areas of work, mobility, and ADL limitations. The prevalence of work disability, based on the decision to stop working, among people with arthritis approaching retirement, was estimated from the 1992 Health and Retirement Study (HRS) (31). More than 40% of 8.78 million people ages 51-61 reporting arthritis in 1992 reported work disability.…”
Section: National Studies On the Economic Costs Of Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 presents findings from national samples of older adults living in the community on disability measures in the areas of work, mobility, and ADL limitations. The prevalence of work disability, based on the decision to stop working, among people with arthritis approaching retirement, was estimated from the 1992 Health and Retirement Study (HRS) (31). More than 40% of 8.78 million people ages 51-61 reporting arthritis in 1992 reported work disability.…”
Section: National Studies On the Economic Costs Of Arthritismentioning
confidence: 99%
“…More than 40% of 8.78 million people ages 51-61 reporting arthritis in 1992 reported work disability. Work disability rates as high as 70% were found among people with arthritis who additionally reported activity limitations (31).…”
Section: National Studies On the Economic Costs Of Arthritismentioning
confidence: 99%
“…Arthritis is also known to be associated with significant disability and economic burden. Arthritis accounts for one-eighth of all restricted activity days in the US adult population, causes large health-care and work disability costs, and leads to notable decrements in social role performance (Guccione et al 1994;Yelin, 1995;Yelin & Callahan, 1995;Lawrence et al 1998;Dunlop et al 2004;Stang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 5 percent of the population and 30 percent of the arthritis population report work limitations resulting from the disease (Lorig, 2007). Yelin (1995) reported that disability rates for individuals with musculoskeletal conditions range from 38 to 72 percent.…”
Section: Anti-arthritic Medications and Labor Supplymentioning
confidence: 99%